Strategi Negara Kawasan Asia Tenggara dalam Pemulihan Ekonomi Pasca Pandemi Covid-19 - Ayu Wandira; Dian Fitriani; Evita Muftiah Fauzi; Oot Hotimah (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
The aim of this research is to analyze the strategies of countries in the Southeast Asia region in economic recovery after the COVID-19 pandemic. The method used in this research uses a qualitative approach with secondary data as a source of analysis. The research results show that the post-COVID-19 pandemic economic recovery strategy implemented by countries in the Southeast Asia region, especially Indonesia, Malaysia, Singapore, Vietnam and the Philippines, is in the form of fiscal and monetary policies, private sector support, public health management and intensifying tourism. Meanwhile, the current economic conditions in the country have shown gradual recovery.